2008
DOI: 10.1103/physrevlett.100.170505
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Generation of Entangled Photons by Controlling Cavity Bipolariton States

Abstract: We theoretically investigate entangled-photon generation via a biexciton in a planar microcavity. Owing to strong exciton-photon coupling, the biexciton in the cavity produces a bound two-cavity-polariton state (cavity bipolariton). Entangled photons are generated by the cascade decay of the cavity bipolariton. We propose a novel scheme for highly efficient entangled-photon generation by controlling the cavity bipolariton states. It is shown that highly efficient generation can be achieved when a weak cavity b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 15 publications
1
25
0
Order By: Relevance
“…These observations can be understood as a polaritonic analog of the Feshbach resonance: "polaritonic Feshbach resonance" [12]. For device applications of semiconductor microcavities, the enhancement of the non-linearity might be useful for a non-classical photon generation [10,14]. Additionally, the polaritonic Feshbach resonance is also interesting in terms of some questions of fundamental physics including a collective paring [15] and a formation of bose polarons [16].…”
Section: Introductionmentioning
confidence: 99%
“…These observations can be understood as a polaritonic analog of the Feshbach resonance: "polaritonic Feshbach resonance" [12]. For device applications of semiconductor microcavities, the enhancement of the non-linearity might be useful for a non-classical photon generation [10,14]. Additionally, the polaritonic Feshbach resonance is also interesting in terms of some questions of fundamental physics including a collective paring [15] and a formation of bose polarons [16].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, electronic exciton-polariton interactions of quantum wells in microcavity 28 has also been reported. Bipolaritons generated using four wave mixing techniques have been used as efficient entangled photon source 29,30 .…”
Section: Introductionmentioning
confidence: 99%
“…9 represent the backward emission from the cavity structure, where the cavity mode frequency is tuned to ω T , γ ex = 0.5 meV, and the periods of the incident and transmitted sides are 4 and 16, respectively (Q-factor is 50). This system corresponds to the weak bipolariton regime 15,16 (but the strong-coupling regime of excitons and photons), where the energy splitting between polariton and biexciton levels is small compared with their broadening. This situation is in contrast to that in Refs.…”
Section: With Dbr Cavitymentioning
confidence: 99%
“…While one solution is using a single quantum dot as a deterministic source, [4][5][6][7][8] for the pursuit of highpower generation there is a proposal of using an optical cavity embedding an excitonic quantum well for the improvement of generation efficiency. 15,16 Furthermore, owing to the rapid radiative decay by the exciton superradiance (enhancement of interaction volume between excitons and photons), 17,18 we have theoretically revealed that the trade-off problem can be resolved simultaneously realizing a high generation efficiency by using an optical cavity embedding an excitonic layer in nano-to-bulk crossover regime.…”
mentioning
confidence: 99%